a + 3 a = 6 6 a
Find the number of solutions of a for the above equation.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Great problem!
As always, when manipulating an equation, we have to careful and check that we didn't introduce extraneous solutions. In this case, we could better justify the substitution by saying "The domain of a is [ 0 , ∞ ) . Thus, we can use the bijective substitution a = x 6 , x ∈ 9 0 , ∞ ) . This explicitly explains how to deal with the solutions of the equation in x .
@Otto Bretscher Even I am back to roots! :P
Exactly Same Way.
I think this is wrong because (-3)^6 of course satisfies the equation and a polynom 3rd grades ALWAYS has three roots - in our case one real and two (conjugate) complex ones!!!
Log in to reply
Can you show your working how ( − 3 ) 6 satisfies the equation?
Log in to reply
Of course: ((-3)^6)^0.5+((-3)^6)^(1/3)=(-3)^3+(-3)^2=-27+9= -18=6*((-3)^6)^(1/6)=-18 q.e.d.
Log in to reply
@Andreas Wendler – 6 ( − 3 ) 6 = − 3 .
Log in to reply
@Nihar Mahajan – Surely this is: ((-3)^6)^(1/6)=(-3)^(6*1/6))=(-3)^1=-3 ;-)
Log in to reply
@Andreas Wendler – You are not allowed to take square root like that. x 2 = ∣ x ∣ and not x . You may read this wiki
Log in to reply
@Nihar Mahajan – The range of the solutions of your task is NOT restricted to real numbers! Have you ever heard about complex numbers?
Log in to reply
@Andreas Wendler – Do you know the proper definition of taking a square root?
Log in to reply
@Nihar Mahajan – sqrt(1)=1 and sqrt(-1)=i. ;-)))
Log in to reply
@Andreas Wendler – Fine , since you are using complex numbers , have a look at this:
6 ( − 3 ) 6 = 6 3 6 i 1 2 = 6 3 6 × 1 = 3 × 1 = 3
Log in to reply
@Nihar Mahajan – i 1 2 = + 1 < > − 1 = > Y o u f o o l !
Log in to reply
@Andreas Wendler – Unfortunately you are absolutely out of idea. That's why I advice the following link for you:
https://www.youtube.com/watch?v=JdbZYrxL5OU
@Nihar Mahajan – − 3 = 3 e i π = > ( − 3 ) 6 = 3 6 e 6 i π = > ( − 3 ) 6 ) 6 1 = 3 e i π = − 3
Other questions?
For clarity, you might want to write "Find the number of solutions a ≥ 0 for the above equation" since your solution does not apply to negative a .
Problem Loading...
Note Loading...
Set Loading...
First substitute a = x 6 to get cleaner form of the equation:
x 3 + x 2 = 6 x ⇒ x 3 + x 2 − 6 x = 0 ⇒ x ( x 2 + x − 6 ) = 0 ⇒ x ( x − 2 ) ( x + 3 ) = 0
Now this gives us x = { 0 , 2 , − 3 } ⇒ a = { 0 , 6 4 , ( − 3 ) 6 } . But why is the answer 2 ?
This is because when a = ( − 3 ) 6 does not satisfy the given equation and is kinda extraneous solution. Hence a = { 0 , 6 4 } and only 2 solutions for a in the equation.